1972
DOI: 10.1029/wr008i004p00931
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow simulation: 2. The broken line process as a potential model for hydrologic simulation

Abstract: This paper deals with the theory of the broken line process and its applications in the simulation of stochastic sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 4 publications
(1 reference statement)
0
30
0
1
Order By: Relevance
“…Several types of models, such as fractional Gaussian noise (FGN) models (Mandelbrot, 1965;Mandelbrot & Wallis, 1969a,b,c), fast fractional Gaussian noise models (Mandelbrot, 1971), broken line models (Ditlevsen, 1971;Mejia et al, 1972), fractional autoregressive integrated moving-average models (Hosking, 1981(Hosking, , 1984, and symmetric moving average models based on a generalized autocovariance structure (Koutsoyiannis, 2000), have been proposed to reproduce the Hurst phenomenon when generating synthetic time series (see also Bras & Rodriguez-Iturbe, 1985).…”
Section: Open For Discussion Until 1 February 2003mentioning
confidence: 99%
“…Several types of models, such as fractional Gaussian noise (FGN) models (Mandelbrot, 1965;Mandelbrot & Wallis, 1969a,b,c), fast fractional Gaussian noise models (Mandelbrot, 1971), broken line models (Ditlevsen, 1971;Mejia et al, 1972), fractional autoregressive integrated moving-average models (Hosking, 1981(Hosking, , 1984, and symmetric moving average models based on a generalized autocovariance structure (Koutsoyiannis, 2000), have been proposed to reproduce the Hurst phenomenon when generating synthetic time series (see also Bras & Rodriguez-Iturbe, 1985).…”
Section: Open For Discussion Until 1 February 2003mentioning
confidence: 99%
“…However, by choosing parameters carefully, it can be shown that it is possible to replicate the observed Hurst phenomenon over a large range of n. O'Connell [33] was an early exponent of this idea; specifically, he used an ARMA(1, 1) model which could (roughly) preserve a given first-lag auto-correlation as well as h. For completeness, we mention that other modelling approaches were investigated to try and replicate the Hurst phenomenon. One such model was the so-called "broken-line" process detailed by Rodriguez-Iturbe et al [62], Garcia et al [63], and Mejia et al [64,65] which sought to preserve a twice differentiable spectrum. This was criticised by Mandelbrot [66] and did not prosper.…”
Section: Reactions To Mandelbrot's Modelmentioning
confidence: 99%
“…Ces modèles à mémoire longue incluent les modèles « bruit Gaussien » (MANOELBROT et WALLIS, 1969a , b, c), de « ligne brisée»» (MEJIA et al, 1972), «niveau variable» (BOES et SALAS, 1978;BALLERINI et BOES, 1985), et « autorégressif et moyennes mobiles sur différen-ces fractionnaires »» (GRANGER, 1980 ;GRANGER et JOYEUX, 1980 ;HOSKING, 1981HOSKING, , 1984HOSKING, , 1985Ll et McLEOD, 1986). Plusieurs de ces modèles à mémoire longue sont aussi présentés dans des ouvrages d'hydrologie stochastique (KOTTEGODA, 1980 ;SALAS et al, 1980 ;BRASS et RODRIGUEZ-ITURBE, 1984 ; HIPEL et MCLEOD, 1990).…”
Section: Introductionunclassified